The Hidden Moral Message in the Hyperreality of the Novel 'Al-Bintū Allatī Lā Tuhibbu Ismahā' - Nur Illiyyin Setya Mufti; M Anwar Masadi; Fika Burhan Tajalla (University of Darussalam Gontor, 2023)
This research aims to discover various moral messages within the series of hyperreality situations in the novel